1997
DOI: 10.1108/14635789710184970
|View full text |Cite
|
Sign up to set email alerts
|

How valuers use the value opinions of others

Abstract: Theory suggest that valuers will rely on previous values estimates in the face of greater market uncertainty. Nevertheless recent research has provided evidence that experienced real estate valuers (appraisers) working in geographic areas familiar to them may not be influenced by the previous value judgement of other, anonymous experts. Presents a study which extends the previous investigation by examining appraisers valuing property in geographic areas unfamiliar to them, appraisers who therefore face signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 4 publications
5
78
0
Order By: Relevance
“…In the real estate literature, Northcraft and Neale (1987) present evidence of anchoring in property pricing that is similar for both amateurs and real estate professionals. Black and Diaz (1996), Diaz and Hansz (1997), Diaz and Wolverton (1998), and Diaz, Zhao and Black (1999) also find evidence of an anchoring effect in real estate prices. 1 Bokhari and Geltner (2011) provide evidence that loss aversion plays a role in CRE pricing that varies across market participants and real estate cycles.…”
Section: Background Literaturementioning
confidence: 95%
“…In the real estate literature, Northcraft and Neale (1987) present evidence of anchoring in property pricing that is similar for both amateurs and real estate professionals. Black and Diaz (1996), Diaz and Hansz (1997), Diaz and Wolverton (1998), and Diaz, Zhao and Black (1999) also find evidence of an anchoring effect in real estate prices. 1 Bokhari and Geltner (2011) provide evidence that loss aversion plays a role in CRE pricing that varies across market participants and real estate cycles.…”
Section: Background Literaturementioning
confidence: 95%
“…Much of the intrapersonal judgement studies included are conducted by means of an experimental design first used by Diaz (1997) and Diaz and Hansz (1997). Their experiments typically measure the effect of a bias-triggering intervention (such as a fictive reference point or client request) on market value estimates produced by valuers who are divided into a treatment group and a control group.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Anchoring bias occurs as the human brain seeks cognitive shortcuts (i.e. heuristics) to overcome the limited amount of short-term memory in light of information ambiguity (Diaz & Hansz, 1997). 2 Depending on the level of objective and factual information available to the valuer, individual valuers must rely to some extent on their own judgement skills and hence may (sub)consciously be exposed to heuristic bias in their value decision (Joslin, 2005).…”
Section: Professional Autonomy In Real Estate Valuationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, behavioural studies have found that property appraisers who work in unfamiliar markets anchor their valuations on anonymous experts' opinions (Diaz & Hansz, 1997, 2001, but this anchor behaviour is not found in familiar markets (Diaz, 1997). Diaz and Hansz suggest that when property appraisers experience increased uncertainty, they use information they would not normally consider reliable.…”
Section: Introductionmentioning
confidence: 99%